KONSEP IMAN, ISLAM DAN TAQWA: (Analisis Hermeneutika Dilthey terhadap Pemikiran Fazlur Rahman) - Intan Fitriya, Nailah Farah , (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
The concept of Faith and Islam is one of the important teachings in Islam. In fact, it has become an outline of Islam which consists of three pillars, namely the Aqeedah (Pillars of Faith), Sharia (Pillars of Islam), and Morals (Ihsan). However, Fazlur Rahman provides another formula for the concept, namely Faith, Islam and Taqwa. So, the purpose of this research is to understand the concepts of Faith, Islam and Taqwa based on Fazlur Rahman's thinking. This research refers to Fazlur's library of sources used in analyzing the theory of hermeneutics. The hermeneutic theory used in this research is Dilthey's hermeneutics. The results of this study are: 1) Fazlur Rahman's biography is arranged in the frame of experiences-understanding which consists of all Fazlur Rahman's life experiences, evolution of Fazlur Rahman's thoughts and works, and Fazlur Rahman's constellation of contemporary Arab thinkers who classify him as a reconstructive reformative thinker. 2) Dilthey's hermeneutical analysis of Fazlur Rahman's thinking is to produce an understanding that Fazlur Rahman's entire life experience influences his main idea, neo-modernism. Then it is arranged in the form of a systematic methodology, namely the double movement theory which is used to examine the basic principles of the Qur’an in the form of ethics. The key terms of the Qur'anic ethics are Faith, Islam and Taqwa. So that the formula of Faith and Islam according to Fazlur Rahman is different from the understanding of Faith and classical Islam.